Effect of Inhomogeneous Mechanical Properties on the Stress-Strain Field at the Crack Tip and Crack Growth Direction in Dissimilar Metal Welded Joints - Shuang Wang; Hongkui Zhang; Zhe Ju; Bing Li; Fandong Chen; Fei Han (Science and Technology of Nuclear Installations)
In the failure analysis and safety assessment of dissimilar metal welded joints, the mechanical heterogeneity of local regions is usually ignored and limited sampling locations are selected. The mechanical behavior of the crack tip region is the main variables affecting the environmentally assisted cracking behavior, and it is crucial for understanding the impact of mechanical heterogeneity on the local stress-strain state at the crack tip in welded joints. In this study, the effect of mechanical heterogeneity on the local mechanical behavior at the crack tip and on the stress-strain condition at the crack tip front for different crack sizes was investigated through finite-element simulations based on user-defined material subroutines. The local mechanical behavior of an interface region and crack propagation direction with mechanical heterogeneity and a series of initial crack locations were analyzed. The results show that mechanical heterogeneity has a significant effect on the mechanical condition and growth path of cracks at different sampling locations. The interaction between the mechanical heterogeneity around the crack and the crack depth determines the stress and plastic strain in front of the crack tip, which causes a substantial change in the crack growth path. The interface cracks have high stress and plastic strain; thus, the interface is often the weak position where damage occurs. To guarantee a reliable integrity assessment of cracks in mechanically heterogeneous interface regions, local mechanical properties related to crack locations should be determined and utilized.